Upaya Meningkatkan Hasil Belajar IPA Peserta Didik pada Masa Pandemi Covid-19 Melalui Project Based Learning di Kelas VI.C T.P. 2020/2021 SD Negeri 04 Payakumbuh - Zuharnelhas Zuharnelhas (Journal on Education, 2021)
Science learning is a learning content that is favored by students. Because the material is directly related to everyday life. Online learning causes students' interest in learning to decrease. So that the value of the science content obtained is low. It is hoped that the Project Based Learning model can help improve student learning outcomes in science learning content. The implementation of the Project Based Learning model consists of five activities, namely: determining basic questions, designing project plans, compiling schedules, monitoring students and project progress, testing results, evaluating experiences, finalizing, and publishing products. The data obtained are sourced from student data, teachers, and documentation. The data collection procedure used observation instruments, field notes, tests, peer observation, collaboration, and documentation. The results obtained can be seen from three sides. The first is from the implementation side related to the interest of students in carrying out learning shows an increase, secondly the formation of student character is reflected in the assignment of assignments, and third, there is an increase in students' science learning outcomes with the Project Based Learning model in class VI.C SD Negeri 04 Payakumbuh.